Hydaticus aequalis sp. n. and a new record of H. devexus Trémouilles, 1996 from Brazil (Coleoptera, Dytiscidae, Hydaticini) - Benetti, Cesar J.; Gustafson, Grey T.; Hamada, Neusa; Short, Andrew Edward Z. (Zootaxa, 2020)
Hydaticus aequalis sp. n. is described from Brazil, where it was recently discovered in the central lowlands region of the Amazon forest. The new species differs from all other Neotropical congeners by its uniformly brown dorsal surface and the shape of medial lobe. The dorsal habitus and male genitalia are illustrated, and a distribution map is provided. The habitat, a small stream and associated forest pool, is illustrated and described. In addition, a new record of H. devexus Trémouilles, 1996, previously known from a single specimen, is reported from the highlands of northeastern Brazil, and a modified key to Neotropical species of the genus is provided.